Wawasan Al-Qur’an Tentang Kesehatan - Sumarno; Haddade, Hasyim; Damis, Rahmi (Jurnal Pendidikan Islam, 2022)
Health is a treasure that has no value for humans, because with health everyone can carry out their daily activities without anyone limiting it. In the Big Indonesian Dictionary, health is divided into three types; physical health, mental health (psychic), and public health. These three kinds of health, should be maintained as well as possible. So that later it will create a life that we all desire together, namely the happiness of the world, and the happiness of the hereafter. However, there are so many people who do not care about their health. Al-Quran is a cure for all human ailments. Many people think that physical disease isdangerous, but they don't realize that the most dangerous disease is a disease that is in the chest, namely liver disease. If so, then the Quran is the solution.